Unusual presentation of urinary tract infection with gross hematuria and bladder hematoma in pregnancy: a case report - Jain, Kanchi; Shrigiriwar, Mansi; Waikar, Manjushree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
A 21-year-old pregnant patient at 28 weeks gestation presented with gross hematuria, burning micturition, and lower abdominal pain over 2-3 days. Imaging revealed cystitis and bladder hematoma formation. Urinalysis showed leukocytes and numerous red blood cells, while urine culture was negative for significant organism growth. Treatment with injectable antibiotics and continuous bladder irrigation led to symptom resolution. This report highlights an unusual manifestation of urinary tract infection (UTI)-induced bladder hematoma in pregnancy presenting with gross hematuria.